Métodos multimídias no ensino de conceitos de química - Priolli, Thais Moreno (2015)
Multimedia resources can aid in visualizing fundamentals aspects to the teaching chemistry, mainly, by the fact that there are some contents which are of difficult understanding by the students. In addition, those technological tolls motivate and attract students for the study of chemistry, which is currently seen for most students of them as an uninteresting discipline. Therefore, one of the goals of this work is the develop lessons and videos classes, which uses simulation software features of molecules, simulation experiments (virtual chemistry lab) and videos, with possibilities of scientific dissemination and the use of new methodologies. The scientific dissemination occurred through the video lectures which are available on the Internet, with reflections of data obtained. The classroom with multimedia resources were developed with high school students and a licensed in Chemistry, with the purpose of encourage future teachers of Chemistry to the use of multimedia resources as possibilities in teaching work. In this research, were used questionnaires seeking to verify the opinions of students and teachers basic education, and of the licensed in Chemistry, who were subjected to this research, about the use of multimedia resource in teaching. The results indicated some contribution of the multimedia resources likewise, as well as some difficulties.